GSK‐3β inhibitor TDZD‐8 prevents reduction of aquaporin‐1 expression via activating autophagy under renal ischemia reperfusion injury. Issue 8 (27th July 2021) - Liu, Qiaojuan; Kong, Yonglun; Guo, Xiangdong; Liang, Baien; Xie, Haixia; Hu, Shan; Han, Mengke; Zhao, Xiaoduo; Feng, Pinning; Lyu, Qianqian; Dong, Wei; Liang, Xinling; et al.
Abstract: Renal ischemia/reperfusion (I/R) injury is a main cause of acute kidney injury (AKI). Aquaporin (AQP)‐1 water channel in the kidney is critical for the maintenance of water homeostasis and the urinary concentrating ability. Increasing evidence supports an important role of autophagy in the pathogenesis of AKI induced by renal I/R. The purpose of the present study is to investigate whether activation of autophagy prevents downregulation of AQP1 protein induced by renal I/R and potential molecular mechanisms. Renal I/R induced consistently reduced protein expression of AQP1, 2, and 3, as well as sodium cotransporters Na + ‐K + ‐2Cl − cotransporter and α‐Na, K‐ATPase, which was associated with increased urine output and decreased creatinine clearance in rats. Renal I/R also suppressed autophagy and increased inflammatory responses in the kidney. 4‐Benzyl‐2‐methyl‐1, 2, 4‐thiadiazolidine‐3, 5‐dione (TDZD‐8), the glycogen synthase kinase‐3β inhibitor, ameliorated renal injury under I/R, activated autophagy and markedly increased expression of AQPs and sodium transporters in the kidney, which was associated with improved urine output and creatinine clearance in rats. Hypoxia/reoxygenation (H/R) induced suppression of autophagy and downregulation of AQP1 in murine inner medullary collecting duct 3 (IMCD3) cells, which was fully prevented by TDZD‐8 treatment. Inhibition of autophagy by 3‐methyladenine or Atg5 gene knockdown attenuated recovery of AQP1 protein expression induced by TDZD‐8 in IMCD3 cells with H/R. Interleukin‐1 beta (IL‐1β) decreased the abundance of AQP1 protein in IMCD3 cells. H/R induced increases in protein expression of nod‐like receptor pyrin domain‐containing 3 and IL‐1β, which was reversed by TDZD‐8. In conclusion, TDZD‐8 treatment prevented downregulation of AQP1 expression under renal I/R injury, likely via activating autophagy and decreasing IL‐1β production.